Sebuah Kajian Kolaborasi dan Graf Komunikasi Penulsi pada Jurnal IJEIS (Indonesian Journal of Electronic and Instrumentation System), Universitas Gadjah Mada - Kriswanto, Y. Rudi; Erliyana, Ella; Adiguna, I Ketut Gunadi; Cahyani, Indah Rachma (UI Scholars Hub, 2020)
This study aims among others; to know the level of author collaboration; the most prolific writer; the amount of information on the communication graph; the synthesis point; to know the relationship between productive authors with a synthesis point. Data collection is done by taking the author of the article in the journal IJEIS UGM in the 2015-2017 edition year. To find out the level of collaboration authors required the theory written Subramanyam. Then to map the relationship of collaboration between authors required communication graph. By applying Brillouin formulation, the communication graph can be determined synthesis point the calculation results show the writer's collaboration rate of 98%. The author with the highest productivity of 11 was obtained by author Raden Sumiharto. The total amount of information in the communication graph is 16.10 bits. Nodes 53 are the nodes that have the highest synthesis point, while nodes 53 are Raden Sumiharto. From the results of the study also known that the most productive writers also have the highest synthesis point value.